Photoprotective Pigments in a Pond Morph of Daphnia middendorffiana - Luecke, Chris; O'Brien, W. John (ARCTIC, 1983)
Two morphs of Daphnia middendorffiana, a pigmented form with a dorsal black patch found commonly throughout Alaska in ponds and a nonpigmented form found in some lakes in the same vicinity, were exposed to natural sunlight conditions. The nonpigmented morph suffered higher mortality in sunlight than did the dark morph, and the black patch was lost when animals were protected from exposure to light. The pigmentation appears to protect Daphnia middendorffiana from the harmful effects of natural radiation. This pigmentation pattern is an adaptation to living in shallow ponds exposed to high light intensities and few visual-feeding predators.Key words: light toxicity, Daphnia middendorffiana, pigmented pond morph, Alaska, arctic ponds Mots clés: toxicité de la lumière, Daphnia middendorffiana, forme pigmentée, Alaska, mares arctiques